Analisis Hidraulik Sistem Drainasi di Lahan Gambut Lapangan Minyak Duri Caltex Pacific Indonesia Riau - Budi Wignyosukarto (Forum Teknik, 2004)
Duri Field covers an area of approximately 9500 hectars that will be developed with steam injection (steamflooding) into I3 areas. During rainy season, several part of the Duri Field are inundated by rain water that disturbing the operation of the exploration. The problent of inundation in The Duri Field Area that endanger the CPI focilities could be caused by limited canal capacity and bad performance of hydraulic stuctures, change of Rainfall – Runoff relation due to the change of infiltration capacity of the watershed area, land subsidence due to excess load and ground water extraction. Unfurtunately, part of the Duri Field is laid down on the peat soil dome that is subject to land subsidence under an intensive drainage.The important issues in developing a peat lands are land subsidence due to shrinkage and changes to peat properties. Oxidative changes are irreversible. The effort of draining the excess run-off water by increasing the existing canal capacity shall in no way cause for over-draining and lowering the gyound water level during dry season. The drainage system shall be designed to maintain this ground water level to avoid any soil subsidence and drying the peat. An hydraulic simulation to analyze the probable ground waler extraction is performed.The result of conventional hydraulic simulations require a widening and deepening part of the primary canal. This channel improvement will increase the drainability, but in the other side could prontote the lowering of water table, peat oxidation and land subsidence. Instead of channel improvement, increasing the elevation of Duri Field facilities above flood level and developing collector drainage channel along the border of Duri Field are suggested. Keywords: drainage, peat soil, subsidence.